DOES ARTIFICIAL INTELLIGENCE HELP WOMEN IN INTERNATIONAL ARBITRATION? : A FEW REMARKS ON DIVERSITY IN ARBITRAL TRIBUNALS - Łągiewska, Magdalena (International Journal of Law in Changing World, 2025)
New technologies are transforming international arbitration, with institutions adopting digital tools and case management systems to streamline proceedings. Artificial Intelligence (AI), in particular, is reshaping the field by introducing innovation-driven solutions that enhance efficiency. This article explores AI’s role in international arbitration, focusing on its potential to improve gender diversity in the appointment of arbitrators. Specifically, it examines whether AI-based selection tools can reduce discrimination and challenge entrenched stereotypes, such as the dominance of the “male, pale, and stale” profile in arbitral tribunals. The study suggests that AI could mark a turning point by promoting more inclusive selection processes. However, this potential hinges on the development of unbiased, well-programmed AI systems. While AI offers a promising path toward increasing diversity, its effectiveness will depend on its ability to avoid replicating existing biases and ensure fairness in the selection and appointment of women arbitrators. _____ ¿AYUDA LA INTELIGENCIA ARTIFICIAL A LAS MUJERES EN EL ARBITRAJE INTERNACIONAL? ALGUNAS COMENTARIOS SOBRE LA DIVERSIDAD EN LOS TRIBUNALES ARBITRALES Las nuevas tecnologías están transformando el arbitraje internacional, y las instituciones están adoptando herramientas digitales y sistemas de gestión de casos para agilizar los procedimientos. La Inteligencia Artificial (IA), en particular, está transformando el campo al introducir soluciones innovadoras que mejoran la eficiencia. Este artículo explora el papel de la IA en el arbitraje internacional, centrándose en su potencial para mejorar la diversidad de género en el nombramiento de árbitros. En concreto, examina si las herramientas de selección basadas en IA pueden reducir la discriminación y desafiar estereotipos arraigados, como el predominio del perfil "masculino, pálido y rancio" en los tribunales arbitrales. El estudio sugiere que la IA podría marcar un antes y un después al promover procesos de selección más inclusivos. Sin embargo, este potencial depende del desarrollo de sistemas de IA imparciales y bien programados. Si bien la IA ofrece una vía prometedora para aumentar la diversidad, su eficacia dependerá de su capacidad para evitar replicar los sesgos existentes y garantizar la equidad en la selección y el nombramiento de árbitras. _____ 人工智能能否助力女性参与国际仲裁？关于仲裁庭多元化的几点思考 新技术正在改变国际仲裁，各机构纷纷采用数字化工具和案件管理系统来简化程序。尤其是人工智能 (AI)，它通过引入创新驱动的解决方案来提升效率，重塑了这一领域。本文探讨了人工智能在国际仲裁中的作用，重点探讨了其在仲裁员任命过程中提升性别多样性的潜力。具体而言，本文考察了基于人工智能的遴选工具能否减少歧视，并挑战根深蒂固的刻板印象，例如仲裁庭中“男性化、苍白、陈腐”的形象占据主导地位。该研究表明，人工智能可以通过促进更具包容性的遴选流程，标志着一个转折点。然而，这种潜力取决于开发出公正、程序完善的人工智能系统。虽然人工智能为提升多样性提供了一条充满希望的道路，但其有效性取决于它能否避免复制现有的偏见，并确保女性仲裁员的选拔和任命的公平性。